Effective GH Replacement With Once-weekly Somapacitan vs Daily GH in Children with GHD: 3-year Results From REAL 3 - Sävendahl, Lars; Battelino, Tadej; Højby Rasmussen, Michael; Brod, Meryl; Saenger, Paul; Horikawa, Reiko (The journal of clinical endocrinology and metabolism, 2022)
Abstract Context Current GH therapy requires daily injections, which can be burdensome. Somapacitan is a long-acting GH derivative in development for treatment of GH deficiency (GHD). Objective Evaluate the efficacy, safety, and tolerability of once-weekly somapacitan after 3 years of treatment. Design A multicenter, randomized, controlled, phase 2 study comparing somapacitan and once-daily GH for 156 weeks (NCT02616562). Setting Twenty-nine sites in 11 countries. Patients Fifty-nine children with GHD randomized (1:1:1:1) and exposed to treatment. Fifty-three children completed the 3-year period. Interventions Patients received somapacitan (0.04 [n = 14], 0.08 [n = 15], or 0.16 [n = 14] mg/kg/wk) or daily GH (n = 14) (0.034 mg/kg/d, equivalent to 0.238 mg/kg/wk) subcutaneously during the first year, after which all patients on somapacitan received 0.16 mg/kg/wk. Main Outcome Measures Height velocity (HV) at year 3; changes from baseline in height SD score (HSDS), HVSDS, and IGF-I SDS. Results The estimated treatment difference (95% CI) in HV for somapacitan 0.16/0.16 mg/kg/wk vs daily GH at year 3 was 0.8 cm/y (−0.4 to 2.1). Change in HVSDS from baseline to year 3 was comparable between somapacitan 0.16/0.16 mg/kg/wk, the pooled somapacitan groups, and daily GH. A gradual increase in HSDS from baseline was observed for all groups. At year 3, mean HSDS was similar for the pooled somapacitan groups and daily GH. Change from baseline to year 3 in mean IGF-I SDS was similar across treatments. Conclusions Once-weekly somapacitan in children with GHD showed sustained efficacy over 3 years in all assessed height-based outcomes with similar safety and tolerability to daily GH. A plain language summary (1) is available for this study. Clinical trial information This study has been registered at ClinicalTrials.gov, number NCT02616562 (REAL 3).